The Differences Of Ramayana Performance In Indonesia (Prambanan) And Myanmar (Fine Arts Department) (A Comparative Study) - , WIN MAW OO; , Dr. Rr. Paramitha Dyah F., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis aims to understand the aspects of the differences of Ramayana performance between Sendratari Ramayana Prambanan and Myanmar Yama Zat Taw. For this purpose, the study focuses on the Ramayana ballet performances held on the outdoor stage of Prambanan temple, Yogyakarta, Indonesia and the Myanmar Ramayana performance (Yama Zat Taw) that presented from the Department of Fine Arts of the Ministry of Culture, Myanmar. To be able to have a total comprehension of the issue, this thesis applies the multidisciplinary analysis, and studies the matter from the viewpoints of comparison, anthropology, and literature. The comparison viewpoints enable the writer to understand the similarities and the differences. The anthropological angle is used to find out the structural background of the Ramayana performances. Literary analysis is also used to reveal the cultural values of the Ramayana performance. The result of this study indicates that the differences of Ramayana performance are the style of performance, characteristic of the dance, costume and background music. Sendratari was influenced by shadow puppet (wayang kulit) while in Yama Zat Taw, some influence of Khon performance from Thailand can be traced back. The style of playing, singing, dancing, and melody are all different from each other. That is mainly because of different culture.